Homologous human milk supplement for very low birth weight preterm infant feeding - Grance,Thayana Regina de Souza (2015)
OBJECTIVE: To develop a homologous human milk supplement for very low-birth weight infant feeding, using an original and simplified methodology, to know the nutritional composition of human milk fortified with this supplement and to evaluate its suitability for feeding these infants. METHODS: For the production and analysis of human milk with the homologous additive, 25 human milk samples of 45mL underwent a lactose removal process, lyophilization and then were diluted in 50mL of human milk. Measurements of lactose, proteins, lipids, energy, sodium, potassium, calcium, phosphorus and osmolality were performed. RESULTS: The composition of the supplemented milk was: lactose 9.22±1.00g/dL; proteins 2.20±0.36g/dL; lipids 2.91±0.57g/dL; calories 71.93±8.69kcal/dL; osmolality 389.6±32.4mOsmol/kgH2O; sodium 2.04±0.45mEq/dL; potassium 1.42±0.15mEq/dL; calcium 43.44±2.98mg/dL; and phosphorus 23.69±1.24mg/dL. CONCLUSIONS: According to the nutritional contents analyzed, except for calcium and phosphorus, human milk with the proposed supplement can meet the nutritional needs of the very low-birth weight preterm infant.